The Role of Technology in Promoting Cultural Competence: A Comprehensive Review in Multicultural Education - Muqarramah Sulaiman Kurdi (International Forum of Researchers and Lecturers, 2023)
This study presents a comprehensive review to explore technology's multifaceted role in fostering cultural competence within multicultural education. The primary objective of this study is to address three fundamental research questions: 1) How does the integration of technology enhance cultural competence in multicultural education settings? 2) What challenges and opportunities are associated with utilizing technology to promote cultural competence in diverse educational settings? 3) How can innovative technological approaches be tailored to address specific cultural competencies in education? Adopting a library research approach, an extensive exploration of academic databases and scholarly sources was conducted to gather literature pertinent to the research questions. The descriptive analysis method was employed to synthesize and analyze the collected information, identifying key themes, differences, similarities, and weaknesses among the diverse sources. The findings from this comprehensive review revealed several significant insights. Technology integration was observed to offer opportunities such as personalized learning experiences through AI-driven tools, immersive cultural experiences via Virtual Reality (VR), and global connectivity fostering cross-cultural collaboration. However, challenges like the digital divide, biases in technological tools, language barriers, ethical concerns regarding data privacy, and pedagogical integration shortcomings were highlighted. Moreover, the study underscores the potential of adaptive technologies, multimodal resources, culturally tailored digital content, and aligning technological interventions with culturally responsive pedagogy to address specific cultural competencies. The recommendations emphasize the need for teacher training, inclusive design, curation of diverse and authentic digital content, interdisciplinary collaborations, and ongoing assessment for optimizing technology's role in promoting cultural competence within multicultural education.